Semiotics analysis of signs of virtues and vices in Si Pitung and Robin Hood - Nisa, Choirun; Silalahi, Pininta Veronika (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This research investigates the folktales of Si Pitung and Robin Hood to identify signs of virtue and vice. The study uses these two stories to analyze the meanings of virtues and vices through Pierce's semiotic approach. Employing a descriptive qualitative method, the research describes the signs of virtues and vices within the tales. Pierce's theory serves as the theoretical framework, illustrating the relationship between the object (referent), representamen (words), and interpretant (reference). The objects in the folktales are virtues and vices, while the representamen are the utterances of Si Pitung and Robin Hood. The findings reveal twelve interpretant signs in the folktale utterances, including faith, helpfulness, loyalty, patience, politeness, responsibility, wisdom, steadfastness, courage, greed, revenge, authoritarianism, cruelty, slander, and cunning. The study identifies 9 (nine) types of virtue, namely courage, temperate, generous, patience, friendly, modesty and truthfulness and witty. And four types of vices—surly, boastfulness, cowardice and witty. In Si Pitung, modesty is shown by students towards the teacher, whereas in Robin Hood, modesty is demonstrated by followers towards the leader. This research elucidates how values of virtue and vice are signified and comprehended, and how folktales can reflect and shape societal values. Keyword: semiotics, signs, folktales, triadic relation.